Reading Comprehension Skills and Lexical Knowledge among Second-Year High School Learners of English as a Foreign Language in Azogues - Muñoz Alvarez, Angelica Natali; Cango Patiño, Adriana Elizabeth; Lojan Caicedo, Jocelyn Andrea; Ocampo Arevalo, Thalia Valeria (Ciencia y Reflexión, 2026)
Developing reading comprehension is not easy, but it is essential to foreign language learning. Therefore, researching the elements underlying this process is important in the educational field. This study examined the reading comprehension skills and lexical knowledge of second-year high school learners of English as a foreign language (EFL) at a private school in Azogues at the beginning of the 2025-2026 school year. A quantitative, non-experimental research explored the relationship between these variables. Ninety students participated, selected through convenience, and two achievement tests were administered: one measuring reading comprehension (skimming for gist, scanning for details, inferential reading, and understanding text logic and structure), and another assessing lexical knowledge(lexicon in context, functional vocabulary, lexical sets, and word-definition correspondence). Both instruments adapted from Cambridge and British Council and validated by experts. Descriptive statistics indicated that students performed best in inferential reading, while understanding text logic and structure was challenging. Regarding lexical knowledge, learners demonstrated strong performance in lexical sets but faced difficulties in using vocabulary in context and applying functional vocabulary. Inferential and descriptive analyses were conducted using JAMOVI. Since the normality test showed non-normal distribution, a Spearman correlation was applied. Results revealed a strong, positive, and statistically significant relationship between reading comprehension and lexical knowledge (r= 0.711, p < .001). This suggests that students with richer lexical knowledge tend to achieve higher levels of reading comprehension. These findings highlight the importance of explicit lexicon instruction to support reading development. Further research with larger and more diverse samples is recommended Developing reading comprehension is not easy, but it is essential to foreign language learning. Therefore, researching the elements underlying this process is important in the educational field. This study examined the reading comprehension skills and lexical knowledge of second-year high school learners of English as a foreign language (EFL) at a private school in Azogues at the beginning of the 2025-2026 school year. A quantitative, non-experimental research explored the relationship between these variables. Ninety students participated, selected through convenience, and two achievement tests were administered: one measuring reading comprehension (skimming for gist, scanning for details, inferential reading, and understanding text logic and structure), and another assessing lexical knowledge(lexicon in context, functional vocabulary, lexical sets, and word-definition correspondence). Both instruments adapted from Cambridge and British Council and validated by experts. Descriptive statistics indicated that students performed best in inferential reading, while understanding text logic and structure was challenging. Regarding lexical knowledge, learners demonstrated strong performance in lexical sets but faced difficulties in using vocabulary in context and applying functional vocabulary. Inferential and descriptive analyses were conducted using JAMOVI. Since the normality test showed non-normal distribution, a Spearman correlation was applied. Results revealed a strong, positive, and statistically significant relationship between reading comprehension and lexical knowledge (r= 0.711, p < .001). This suggests that students with richer lexical knowledge tend to achieve higher levels of reading comprehension. These findings highlight the importance of explicit lexicon instruction to support reading development. Further research with larger and more diverse samples is recommended